The effectiveness of non-monetary rewards towards employee's motivation at Department of MARA Kota Kinabalu, Sabah / Mimi Lisa Sapar - Sapar, Mimi Lisa (2009)
The purpose of this research is to study the effectiveness of non monetary rewards towards employee motivation in MARA department Kota Kinabalu, Sabah by looking at the factors that associate with the effectiveness of non monetary rewards as a motivation tool and looking at which type of non monetary rewards that most effective that influence employee motivation. The sample size for the purposes of this study is 35 peoples which are covering the employees in Department of MARA Kota Kinabalu, Sabah. From the findings, it showing that female is the majority respondents in this research an mostly are agree that the variables of fairness, top management support, social reinforcement, and opportunities and flexibility were associate with the effectiveness of non monetary rewards towards employee motivation. Besides, the respondents strongly agree that the recognition and paid time off were the most effective type of non monetary rewards that influence employee motivation as those two rewards were the employee's preferences. It can be concluded that non monetary rewards have the potential to increase the employee motivation within organization even though it did not involve direct payment of cash.